Pengembangan Training Kit Parkir Cerdas Berbasis Esp 32 untuk Meningkatkan Hasil Belajar Peserta Didik pada Praktikum Mikrokontroler SMKN 2 Lamongan - Taufiq Ismail; Ali Nur Fathoni; Farid Baskoro; Fendi Achmad (Educational Journal, 2026)
The limitation of learning media that align with industrial needs has become one of the obstacles in microcontroller practicum learning in Vocational High Schools (SMK). Therefore, Internet of Things (IoT)-based learning media are needed to bridge theoretical concepts with practical applications. This study aimed to determine the validity, practicality, and effectiveness of an ESP32-based Smart Parking Training Kit as a learning medium for microcontroller practicum at SMKN 2 Lamongan. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The developed product was a training kit based on ESP32 integrated with infrared sensors, RFID sensors, servo motors, a 20×4 I2C LCD, and a Telegram Bot-based monitoring system. The research subjects consisted of 35 eleventh-grade students of the Mechatronics Engineering program. The results showed that the training kit was categorized as highly valid, with material expert validation reaching 83.33% and media expert validation reaching 98.61%. The practicality level of the media obtained a percentage of 94.72% in the highly practical category. The effectiveness results indicated that the average cognitive learning outcomes increased from 68.69 in the pretest to 89.49 in the posttest, with the Paired Sample t-Test showing a significance value of < 0.001. The N-Gain analysis obtained an average score of 0.6156 in the moderate category. In the psychomotor aspect, the average student score reached 92.23, which was higher than the minimum mastery criterion (KKM) of 75, while the One Sample t-Test showed a significance value of < 0.001. Based on these findings, it can be concluded that the ESP32-based Smart Parking Training Kit is feasible, practical, and effective as a learning medium for microcontroller practicum to improve students’ learning outcomes in vocational education.